Evaluation of Rural Development Processes in the Lublin Region Using Similarity Measures - Guzal-Dec, Danuta; Zwolińska-Ligaj, Magdalena (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The purpose of this paper is to present the results of the analysis of rural development processes in the Lublin region for the occurrence of convergence or divergence of development based on similarity measures formulated by I. Kudrycka. The results of analysis will help to identify the characteristics of the differences in developmental processes in the region and will provide an indication to the local authorities, responsible for the design and implementation of intraregional policy for the development of rural areas related to the adaptation of tools to aid development of the individual needs of selected groups of areas. The similarity in the local coordinate system (rural municipalities) was characterized within five areas: human capital, the economy, households, infrastructure and environment. This paper describes the method proposed by I. Kudrycka and presents the analysis of estimated similarity measures and their changes over time. The basis for determining the similarity measures were BDL GUS data.